2020
DOI: 10.3382/ps/pez467
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a bioactive olive pomace extract from Olea europaea on growth performance, gut function, and intestinal microbiota in broiler chickens

Abstract: The present study aims to investigate the effects of supplementing broiler diets with a bioactive olive pomace extract ( OE ) from Olea europaea on growth performance, digestibility, gut microbiota, bile acid composition, and immune response. To this end, three hundred and six 1-day-old broiler chickens (Ross 308) were housed in floor pens (6 pens/treatment, with 17 birds/pen). Animals were fed with a standard non-medicated starter diet for 21 D, and from 22 to 42 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 44 publications
(38 reference statements)
8
42
0
Order By: Relevance
“…Moreover, the inclusion of OE increased Bu-1 expression, suggesting a stimulatory effect on humoral immunity. An immunosuppressant effect on IL-8 and a stimulatory effect on Bu-1 have been observed in our previous study with broilers fed an olive pomace extract in the growing phase [17]. Furthermore, increased B-cell markers has been previously described in broiler chickens fed plant extracts rich in polyphenolic compounds [47].…”
Section: Effect Of Olive Pomace Extractsupporting
confidence: 55%
See 3 more Smart Citations
“…Moreover, the inclusion of OE increased Bu-1 expression, suggesting a stimulatory effect on humoral immunity. An immunosuppressant effect on IL-8 and a stimulatory effect on Bu-1 have been observed in our previous study with broilers fed an olive pomace extract in the growing phase [17]. Furthermore, increased B-cell markers has been previously described in broiler chickens fed plant extracts rich in polyphenolic compounds [47].…”
Section: Effect Of Olive Pomace Extractsupporting
confidence: 55%
“…Furthermore, King et al [45] reported no significant differences in broiler performance after supplementing an olive pomace extract in water. By contrast, Herrero-Encinas et al [17] were able to detect higher ADG and better FCR in broiler chickens fed 1000 ppm of a bioactive extract from Olea europaea from 35 to 42 d of age. Moreover, utilization of olive leaf extracts in broilers' diet improved FCR and body weight in the study of Sarica and Ürmez [46].…”
Section: Effect Of Olive Pomace Extractmentioning
confidence: 77%
See 2 more Smart Citations
“…One of the proposed uses of olive oil by-products is in animal feed supplementation, and several studies have tested their effects in various animal species including poultry [13]. In broiler chickens, feed supplemented with alperujo have been demonstrated to improve productive performance parameters [14,15], and enhance redox status in tissues [16,17]. In addition, alperujo has been shown to possess anti-coccidial proprieties [18].…”
Section: Introductionmentioning
confidence: 99%